From famine to food security: Lessons for building resilient food systems - Babu, Suresh Chandra; Dorosh, Paul A. (International Food Policy Research Institute, 2017)
Armed conflict combined with prolonged drought has put about 20 million people at risk of starvation and death in Somalia, South Sudan, Yemen, and northern Nigeria. The international development and aid communities are caught between the enormity of the humanitarian crisis, which demands an estimated US$4.4 billion to address, and the lack of resources forthcoming from donors. Food crises, famine-like conditions, and famines recur with regularity in many developing countries (see Box 1 for definitions of terms). Although the current famines can be largely attributed to conflicts, chronic food insecurity also threatens several other African countries. For example, 6.7 million people were affected by Malawi’s largest food crisis in decades in 2016–2017, and the country remains vulnerable to weather extremes that could create food emergencies (World Bank 2017). In Kenya, food security has deteriorated since the end of 2016 and half of its 47 counties face food shortages (Chatterjee and Mengistu 2017). How do countries prepare to prevent shocks—natural and man-made—from generating food crises? What does it take to break the cycle of chronic food insecurity and build resilient food systems? How have some countries managed to prevent drought from leading to famine? In this brief, we document lessons for building resilient food systems to prevent future famines.